Kewarisan Beda Agama dalam Putusan-Putusan Hakim di Indonesia - Arif Zunzul Maizal; Yusnita Eva; Syaiful Marwan (Al-Qisthu: Jurnal Kajian Ilmu-Ilmu Hukum, 2022)
This study aims to examine cases of inheritance from different religions that have been decided by the Religious Courts, High Religious Courts, and the Supreme Court in Indonesia. Inheritance from different religions can be classified into inheritance from Muslim heirs to non-Muslim heirs and inheritance from non-Muslim heirs to Muslim heirs. This study uses a judicial case study approach by examining five decisions, consisting of two religious court decisions, two cassation decisions, and one Supreme Court jurisprudence. This study shows that in cases of inheritance from non-Muslim heirs to Muslim heirs, religious court judges allow Muslim heirs to receive inheritance. This is in line with the opinion of some fiqh scholars who allow such provisions. Meanwhile, in cases of inheritance of Muslim heirs to non-Muslim heirs, judges at the religious court, high court, and the Supreme Court did not decide this case as an inheritance, but as a mandatory wasiat, so that the provisions prohibiting a Muslim from inheriting a non-Muslim were still obeyed by these judges. while the relationship between the heir and the heir is maintained because the heir still receives the heir's inheritance. The formulation of this obligatory will does not conflict with the opinion of the clergy, because there are no religious requirements in wasiat.